UTILIZATION OF FLUORESCENT NANOPARTICLES FOR MULTIPLEX DETECTING AND MONITORING MICROORGANISMS - Thuần, Tống Kim (Vietnam Journal of Biotechnology, 2011)
We have earned out successfully the labelling of yeast and bacterial cells by fluorescent quantum dots and silica nanoparticles. For yeast cells Lipomyces, the results showed that the uptake of QDs into cells depended on age and number of cells. For young cells (2 days after culture) the QDs were mainly located in vacuoles. For the cells labeled at about 4 days and 15 days after culture, the QDj accumulated in cytoplasm. The fluorescence image of QDs labeled yeast cells were also taken after 2 months storage in dark at room temperature. The results showed that the labeled yeast cells were still alive after two months labeling; the cell size, shape and morphology were in normal state. The QDs accumulated in cytoplasm in the labeled cells. So, it can be sayed that the QDs did not affect cells and they were not harmfiil to the cells. For E. coli 0157:H7 cells the fluorescence image showed that, ratio of silica nanoparticle - labeled cells/total was high. From TEM image, we could see that many silica nanoparticles were binding on the surface of the cell and the binding was inhomogeneously. The emission depended on binding level ofthe nanoparticles on the bacterial cell.